Screening for antimicrobial activity of natural products using a microplate photometer - Devienne, Karina F. [UNESP]; Raddi, Maria Stella Gonçalves [UNESP] (Sociedade Brasileira de Microbiologia, 2002)
A técnica de microdiluição para a determinação da concentração inibitória mínima (CIM) de um produto natural utilizando espectrofotômetro para microplacas foi comparada ao método de diluição seriada em tubo. A CIM da Paepalantina para S. aureus foi a mesma por ambos métodos demonstrando possuir efeito antimicrobiano semelhante ao cloranfenicol.

The microdilution technique, using a microplate photometer, to determine the minimal inhibitory concentration (MIC) for a natural product was compared to the serial tube dilution method. The MIC obtained for Paepalantine against S. aureus was the same by the two methods, showing an antimicrobial effect similar to chloramphenicol.
Triagem da atividade antimicrobiana de produtos naturais utilizando leitor de microplacas
Keywords: Atividade antimicrobiana; microdiluição; método espectrofotométrico; Antimicrobial activity; microdilution; spectrophotometric method